2023
DOI: 10.1098/rsob.220232
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragility at the KMT2A / MLL locus: insights from old and new technologies

Abstract: The Mixed-Lineage Leukaemia ( MLL/KMT2A ) gene is frequently rearranged in childhood and adult acute leukaemia (AL) and in secondary leukaemias occurring after therapy with DNA topoisomerase targeting anti-cancer agents such as etoposide (t-AL). MLL/KMT2A chromosome translocation break sites in AL patients fall within an 8 kb breakpoint cluster region (BCR). Furthermore, MLL/KMT2A break sites in t-AL frequently occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, in our previous cell line‐based study, we found that MPO activity had an approximately three‐fold greater effect on TOP2B‐CC complex formation than on TOP2A. This is significant as TOP2B appears to be required for the majority of etoposide‐induced MLL and RUNX1 chromosomal breaks [10,34,35] in a human lymphoblastoid cell line model and for etoposide‐mediated carcinogenesis in a mouse model [36].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, in our previous cell line‐based study, we found that MPO activity had an approximately three‐fold greater effect on TOP2B‐CC complex formation than on TOP2A. This is significant as TOP2B appears to be required for the majority of etoposide‐induced MLL and RUNX1 chromosomal breaks [10,34,35] in a human lymphoblastoid cell line model and for etoposide‐mediated carcinogenesis in a mouse model [36].…”
Section: Discussionmentioning
confidence: 94%
“…Notably, TOP2-associated t-AL cases often harbour characteristic balanced chromosome translocations [3] including those involving the KMT2A/MLL locus or t (15,17) (PML-RARA), t(8,21)(AML/RUNX1-ETO) and inv(16) (MYH11-CBFB) translocations [7]. These chromosome translocations are believed to occur following DNA DSBs induced by poisoned TOP2 activity [3,[8][9][10] and are crucial early events in the development of these therapy-related leukaemias; the resulting fusion genes, for example MLL-AF9, are able to induce leukaemia in animal models [11,12]. Therefore, a means of specifically protecting bone marrow haematopoietic progenitors and precursors from the DNA damaging effects of TOP2 poisons would have significant clinical benefit.…”
mentioning
confidence: 99%
“…3 Cells with impaired KMT2A function have reduced DNA damage response and increased susceptibility to DNA damage-induced cell death. 4 KMT2A regulates HSC self-renewal and differentiation, and its loss results in reduced production of various blood cell types.…”
mentioning
confidence: 99%